Innovation for sustainability and networking - Gomes, Jorge F.S. (2013)
The current work sought to understand the softer dimensions which constitute the building blocks of innovation networks. In particular, it addressed the individual and social aspects that bond organizations in such networks. Based on interview data collected from 45 entities involved in various innovation networks in three regions in Portugal, the findings revealed that there are three key dimensions at the micro level of analysis which contribute to understand how organization networks emerge and develop. These dimensions constitute the main theoretical contributions of the current research to the emerging field of innovation networks.